L’industrie alimentaire, un des acteurs de l’expertise et de la gestion du risque - Daumas Anne (Oléagineux, Corps gras, Lipides, 2007)
The food industry has for many years set up quality assurance systems based on an expertise on the processes and products implemented and manufactured. For this reason it must be regarded as one of the stakeholders in terms of expertise and risk management. Risk evaluation made by the Agency must help the food industry to strengthen its quality measures, while, on the other hand the industry must be able to share its experience with Agencies and Authorities.